Ionic and biochemical characterization of bovine intervertebral disk. (3rd May 2016) - Martins, Delio Eulalio; Medeiros, Valquiria Pereira; Demerov, Gabriela Feitosa; Accardo, Camila Melo; Paredes-Gamero, Edgar Julian; Wajchenberg, Marcelo; Reginato, Rejane Daniele; Nader, Helena Bonciani; Puertas, Eduardo Barros; Faloppa, Flávio
ABSTRACT: Introduction : Intervertebral disks have been associated with low back pain, and many therapies have been proposed for its treatment. The cellular and molecular knowledge of intervertebral disks composition and precise methods to quantify disk components are important for any type of proposed therapy. Thus, the aim of this study was to correlate glycosaminoglycans presence with the quantitation of cells, ions and collagen fiber distributions in different intervertebral disk sections. Methods : In total, 14 intervertebral disks were used from cattle. All of the disks were dehydrated, separated in seven sections and digested in sodium-free papain buffer. Glycosaminoglycan measurements were performed in the samples according to agarose electrophoresis method; total cells were measured using the PicoGreen® technique, ions were quantified, and collagen fiber birefringence was analyzed with polarized light. Results : Cations Na+ and K+ are more concentrate in the nucleus (Na + = 1688.50 ± 110 mmol/L; K + = 111.9 ± 28 mmol/L) of intervertebral disks than the annulus (Na + = 652.80 ± 75 mmol/L; K + = 55.6 ± 8 mmol/L). A negative correlation between cells number and sodium/potassium was observed ( p < 0.001) Additionally, thin collagen fibers were largest in the nucleus, similar to hyaluronate distribution. Conclusions : The results suggest that annulus fibrosus cells are also sensitive to changes in ionic concentrations such as nucleus pulposus cells. Additionally, hyaluronate is related to thin collagen fibers type II.